Museum Digitisations and Emerging Curatorial Agencies Online Vikings in the Digital Age - Axelsson, Bodil; Cameron, Fiona R.; Hauptman, Katherine; Pietrobruno, Sheenagh (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XV, 138 p. 13 illus., 12 illus. in color.